(untitled) (Journal of Hama University, 2019)
In this study, two DNA extraction methods from Eimeria tenella oocyst was carried out and evaluated by DNA electrophoresis and using the extracts as a template in polymerase chain reaction. The results showed that the quantity of extracted DNA by the first method that depended on mechanical destruction of the oocysts followed by using of commercial kit was less than DNA extracted by the second method, which included mechanical destruction followed by lysis buffer and CTAB solution. On the other hand, PCR reaction targeting β-Actin gene was successfully completed on the both extracted DNA. The performance of RNA extraction method from sporulating oocyst was evaluated as well, this method included mechanical destruction followed by RNA extraction commercial kit to obtain sporozoite RNA and after that cDNA was produced. PCR reactions targeted β-actin and mic2 genes was carried out successfully on cDNA. The result indicats that this method of extraction RNA is efficient and satisfactory.